2021
DOI: 10.1016/j.hazl.2021.100027
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 spillover into hospital outdoor environments

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…These viruses often pose a serious threat to the whole community, resulting in an epidemic or pandemic ( Bishop and Kirkwood, 2008 ; Itagaki et al, 2018 ; Thongprachum et al, 2018 ). The most recent example of the severity of viruses is the SARS-coronavirus 2 (SARS-CoV-2) outbreak ( Achak et al, 2020 ; Gonçalves et al, 2021 ; Zhang et al, 2021 ). Prado et al (2011) detected rotavirus A, human adenoviruses (HAdV), norovirus genogroup I and II, and hepatitis A viruses from two hospital WWTPs located in Rio de Janeiro, Brazil ( Prado et al, 2011 ).…”
Section: Hospital Wastewatermentioning
confidence: 99%
See 1 more Smart Citation
“…These viruses often pose a serious threat to the whole community, resulting in an epidemic or pandemic ( Bishop and Kirkwood, 2008 ; Itagaki et al, 2018 ; Thongprachum et al, 2018 ). The most recent example of the severity of viruses is the SARS-coronavirus 2 (SARS-CoV-2) outbreak ( Achak et al, 2020 ; Gonçalves et al, 2021 ; Zhang et al, 2021 ). Prado et al (2011) detected rotavirus A, human adenoviruses (HAdV), norovirus genogroup I and II, and hepatitis A viruses from two hospital WWTPs located in Rio de Janeiro, Brazil ( Prado et al, 2011 ).…”
Section: Hospital Wastewatermentioning
confidence: 99%
“… Prado et al (2011) detected rotavirus A, human adenoviruses (HAdV), norovirus genogroup I and II, and hepatitis A viruses from two hospital WWTPs located in Rio de Janeiro, Brazil ( Prado et al, 2011 ). Zhang et al (2021) reported a virus count of SARS-CoV-2 ranging between 255 copies/L and 18,744 copies/L detected in the wastewater samples collected from a hospital located in Wuhan, China ( Zhang et al, 2021 ). Likewise, Sibanda and Okoh (2012) reported an average virus count of HAdV ranging between 6.54 × 10 3 (genome copies/L) and 8.49 × 10 4 (genome copies/L), detected in the wastewater collected from a sampling site located near sewage outfall points of Victoria Hospital, South Africa ( Sibanda and Okoh, 2012 ).…”
Section: Hospital Wastewatermentioning
confidence: 99%
“…In theory, SARS-CoV-2 infection via inhalation of aerosols is possible, similar to SARS-CoV infection via aerosolization from the plumbing system in Hong Kong as described earlier in this article. A study found SARS-CoV-2 RNA in soil (0.21 to 0.056 copies of RNA per mg of sample) and aerosols (0.29 to 1.1 copies of RNA per and omit /mm 3 ) in addition to its presence in wastewater (0.26-18.7 copies per mL of sample) and postulated that the virus genetic material was in soil due to deposition and in wastewater due to aerosolization from infected patients at a nearby hospital (Zhang et al, 2021). While Lednicky et al (2020) found that a SARS-CoV-2 strain in air matched the strain from infected patients within a hospital room, Correia et al (2020) pointed out that airborne transmission of SARs-CoV-2 is possible from building ventilation systems.…”
Section: The Fate Of Sars-cov-2 In Wastewatermentioning
confidence: 99%
“…The presence of SARS-CoV-2 in the sewage treatment system (wastewater, soil, and aerosol) of Huoshenshan Hospital is illustrated in Figure . Among 10 wastewater, three aerosol, and two soil samples collected from all reactors (Figure b), three wastewater samples, one aerosol sample, and one soil sample were positive for SARS-CoV-2.…”
Section: Water-related Concerns and Strategies For Controlling Corona...mentioning
confidence: 99%
“…The soil samples collected from 2 m distance to the first regulating reservoir contained a significant level of SARS-CoV-2 RNA (550 copies/g). Notably, SARS-CoV-2 was not detected in surrounding aerosols and soils of Wuchang Cabin Hospital because of the temporary enclosed system, which effectively prevented the spread of SARS-CoV-2 . It is suggested that the appropriate sealing of the wastewater treatment system may prevent the transmission of SARS-CoV-2.…”
Section: Water-related Concerns and Strategies For Controlling Corona...mentioning
confidence: 99%